The Problems of Performing Piety in some Exeter Dissenting Sermons c.1660–1745 - Parry, David (Studies in church history, 2024)
This article explores the theme of hypocrisy in a multi-volume collection of hitherto unstudied manuscript sermons by Exeter Dissenting ministers from the Restoration to the mid-eighteenth century, held by the Devon and Exeter Institution. In these sermons, the theme of hypocrisy is addressed in a variety of senses and contexts, including the imposition by conformists of forms of worship not required by Scripture; the false accusations of hypocrisy made against Dissenters; the insincere performance of piety; the tendency of sinners to justify vice as virtue and virtue as vice; and the incompatibility of persecution with true New Testament Christianity. These sermons trace a move from Reformed orthodoxy towards rational Dissent, with a soteriology that increasingly makes moral performance a condition of final salvation. The possibility of insincere performance of piety and virtue by hypocrites may have created increased anxiety in a context in which soteriology and ethics were increasingly entangled.